Palaeoceanography and sedimentology of a mid-Cretaceous Greensand - Hart, S; Hart, Stephen Francis (1991)
﻿ The Upper Albian (mid-Cretaceous) sediments of the Anglo-Paris Basin display a range of condensation phenomena, including glauconitic and phosphoritic sands, glauconitic intraformational pebble beds, and mineralised nodular hardgrounds. These are interpreted as the result of sedimentation rate fluctuations controlled by small-scale relative sea-level changes of at least regional nature. The regional signal was modified by local tectonics, including occasional synsedimentary faulting and the development of thinned successions and complex condensation horizons over broad submarine highs. Candidate sequence boundaries, marine flooding surfaces and systems tracts are proposed. Episodic, high-energy storm events record a spectrum of storm intensities and periodicities in the Upper Greensand Formation. Storm processes interacted with early submarine lithification to produce a suite of pebble-shell beds, simple and amalgamated coquinas, and storm-scoured hardgrounds. Analysis of shell bed fabrics and taphonomy indicates the important role of high-energy storms in generating a distinct event stratigraphy. Stable isotope analysis has detected a positive secular change in carbon-isotopic ratios within carbonates of dispar zone age, resolved as two smaller positive shifts across nodular hardgrounds. This correlates with the development of organic-rich sediments in a range of settings world-wide. Analytical problems, including silica diagenesis, have been addressed by a series of parallel control studies. Geochemical and petrographic analysis has confirmed the widespread development of glauconitic minerals throughout the Upper Greensand, and has been used to investigate grain evolution in a range of lithologies. A review of the global development of the Cretaceous glauconitic facies has been used to compile depositional models for a range of settings. Volumetric calculations of Cretaceous glauconite production rates have shown secular changes, with peak Aptian to Santonian values linked to transgressions across the broad shelf seas which developed globally during this time of rising sea-levels and sea-level highstand.